A world of many worlds - Cadena, Marisol de la; Blaser, Mario 1966- (Duke University Press, 2018)
Introduction: pluriverse: proposals for a world of many worlds / Mario Blaser and Marisol de la Cadena -- Opening up relations / Marilyn Strathern -- Spiderweb anthropologies : ecologies, infrastructures, entanglements / Alberto Corsín Jiménez -- The challenge of ontological politics / Isabelle Stengers -- The politics of working cosmologies together while keeping them separate / Helen Verran -- Denaturalizing nature / John Law and Marianne Lien -- Humans and Terrans in the Gaia war / Eduardo Viveiros de Castro and Deborah Danowski